The NZASM Tourist Precinct : Tourism Interventions as Catalyst to re-Establish the Cultural Significance of Historic Railway Housing in Pretoria CBD - Karusseit, Catherine (University of Pretoria, 2018)
Mini Dissertation MInt(Prof)--University of Pretoria, 2018.